Piezoelectric‐driven self‐assembling micro air vehicle with bionic reciprocating wings. Issue 9 (1st May 2018) - Zhou, Sui; Zhang, Weiping; Zou, Yang; Ou, Bin; Zhang, Yuying; Wang, Chenyang
Abstract : A 247 mg weight coin‐size piezoelectric‐driven micro air vehicle (MAV) with four symmetrical distributed bionic flexible wings is presented. The MAV is planar designed and monolithic fabricated via film printed circuit, graphic lasering and lamination process, and is able to be self‐assembled by using shape memory polymer (SMP). The SMP can be heated by the flexible circuit and shrink at a large strain, resulting in the self‐folding of hinges and self‐assembly of MAV from 2D shape into 3D shape. The flexible four‐bar mechanism converts the slight vibration of lead zirconate titanate (PZT) actuator into flexible wings' reciprocation, thereby generating lift force. The response characteristics and motion behaviour of the MAV are experimentally tested. Results suggest that the prototype can be self‐assembled to the designed position and achieve a 23.5° reciprocating angle at 134 Hz resonance frequency under 280 V driving signals.